Extraction/exportation of macronutrients by cladodes of ‘Gigante’ cactus pear under different spacings and organic fertilization - Paulo E. R. Donato; Sérgio L. R. Donato; João A. Silva; Aureliano J. V. Pires; Ancilon A. e Silva Junior (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to evaluate the extraction/exportation of macronutrients by cladodes of ‘Gigante’ cactos pear, grown under diferente spacings and doses of cattle manure applied to the soil 600 days after planting. Twelve treatments were used, three spacing (1.00 x 0.50; 2.00 x 0.25 and 3.00 x 1.00 x 0.25 m) and four doses of cattle manure (0, 30, 60 and 90 Mg ha-1 year-1), arranged in a 3 x 4 factorial scheme in randomized blocks, with three replicates. The extraction/exportation of N, P, K, S, Ca and Mg was determined, whose respective values for maximum dry matter production (21.8 Mg ha-1), with a cattle manure dose of 71.8 Mg ha-1 year-1 were: 287.9, 46.2, 924.2, 40.7, 609.7 and 249.1 kg ha-1, 600 days after planting. The amounts extracted/exported from N, P, K and Ca varied independently with spacings and manure doses, while Mg and S were dependent on the interaction between factors. The doses of manure are insufficient to meet the demand of extracted/exported K, Ca and Mg. The increments in the doses promote greater nutrient uptake by the plant. The extracted/exported macronutrients in largest amounts are: K, Ca, N, Mg, P and S, in this order.